2009
DOI: 10.3382/ps.2009-00311
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient dissociation of oxygen from hemoglobin in Tibetan chicken embryos compared with lowland chicken embryos incubated in hypoxia

Abstract: Oxygen is one of the critical determinants for normal embryonic and fetal development. In avian embryos, lack of oxygen will lead to high fetal mortality, heteroplasia, and cardiovascular dysfunction. Tibetan chicken is a breed native to Tibet that could survive and keep higher hatchability regardless of negative effects of hypoxia. Generally, adaptive animals in high altitudes are characterized by higher hemoglobin concentrations and oxygen affinity. In the present study, the capacity of oxygen supply in late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Adaptive lung development has also been reported in mammals living at higher altitudes [38]. E19 is the peak of mortality for embryos growing in both normal and hypoxic conditions [53]. Our data showed relative hypoxic stress at E19 even when embryos are incubated in normal conditions.…”
Section: Discussionsupporting
confidence: 78%
“…Adaptive lung development has also been reported in mammals living at higher altitudes [38]. E19 is the peak of mortality for embryos growing in both normal and hypoxic conditions [53]. Our data showed relative hypoxic stress at E19 even when embryos are incubated in normal conditions.…”
Section: Discussionsupporting
confidence: 78%
“…Another study by Liu et al . [43] showed that the Hb concentration is the most important factor responsible for ensuring oxygen concentration in the blood under hypoxic conditions. In the present study, we found that the hypoxic environment significantly increased the Hb levels on day 14 compared to the normoxia group in AACs, and similar changes in Hb have also been observed in avian embryos [44].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models have been created using a wide variety of species. Compared with models in mammals, studies made in bird embryos 107,108 (such as the chicken) are remarkable because their oviparous nature excludes maternal factors (such as stress, maternal hormones, and maternal nutrition) from the list of potential confounding factors in the model. 109 However, the absence of any feto-placento-maternal interactions and the birds' physiological peculiarities make results obtained in this model hard to extrapolate to other species.…”
Section: Animal Species Used To Study Early Programmingmentioning
confidence: 99%